Highest Ionic Conductivity of BIMEVOX (ME = 10% Cu, 10% Ga, 20% Ta): Computational Modeling and Simulation - Akram La Kilo; Alberto Costanzo; Daniele Mazza; Muhamad Abdulkadir Martoprawiro; Bambang Prijamboedi; Ismunandar Ismunandar (Indonesian Journal of Chemistry, 2020)
BIMEVOX had the potential to play an important role in solid oxide fuel cell, especially as the electrolyte due to their high ionic conductivity. In this work, oxide ion migrations of γ-Bi2VO5.5 and BIMEVOX were simulated using density function theory (DFT), Mott-Littleton method, and molecular dynamic simulation. In γ-Bi2VO5.5, there were oxygen vacancies at the equatorial position in the vanadate layers. These vacancies could facilitate oxide ions migration. The Enthalpy of the oxide migration for γ-Bi2VO5.5 based on DFT calculation was 0.38 eV, which was in a good agreement with experimental results. The γ-Bi2VO5.5 can be stabilized by partial substitution of V5+ with Cu2+, Ga3+, and Ta5+. Defect simulation results using the Mott-Littleton method showed that the total maximum energies of region II were achieved at concentrations of 10, 10, and 20%, respectively for Cu2+, Ga3+, and Ta5+. The calculated concentration of Cu2+, Ga3+, and Ta5+ were in a good agreement with those of experiment results, where the highest ionic conductivity obtained. The results of the molecular dynamics simulation showed that the activation energies of oxide ion migration in γ-Bi2VO5.5 and BIMEVOX (ME = Cu and Ta) respectively were 0.19, 0.21, and 0.10 eV, close to experimental values.